2020
DOI: 10.1007/s10456-020-09730-0
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-2 as a marker of endothelial activation is a good predictor factor for intensive care unit admission of COVID-19 patients

Abstract: Background Coronavirus disease-2019 (COVID-19), a respiratory disease has been associated with ischemic complications, coagulation disorders, and an endotheliitis. Objectives To explore endothelial damage and activation-related biomarkers in COVID-19 patients with criteria of hospitalization for referral to intensive care unit (ICU) and/or respiratory worsening. Methods Analysis of endothelial and angiogenic soluble markers in plasma from patients at admission. Results Study enrolled 40 consecutive COVID-19 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
270
2
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 227 publications
(300 citation statements)
references
References 35 publications
20
270
2
8
Order By: Relevance
“…Infection of endothelial cells could therefore induce endothelial lesions triggering massive activation of coagulation and diffuse microthrombotic process impairing renal function and respiratory gas exchanges. We previously described increased numbers of circulating endothelial cells in COVID-19 patients (4) and an association between circulating biomarkers of endothelial activation in COVID-19 and ICU admission (5). Angiopoietin-2 was also inversely correlated to respiratory system compliance in this study, paving the way of relationship between endothelial dysfunction and pulmonary disease severity.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Infection of endothelial cells could therefore induce endothelial lesions triggering massive activation of coagulation and diffuse microthrombotic process impairing renal function and respiratory gas exchanges. We previously described increased numbers of circulating endothelial cells in COVID-19 patients (4) and an association between circulating biomarkers of endothelial activation in COVID-19 and ICU admission (5). Angiopoietin-2 was also inversely correlated to respiratory system compliance in this study, paving the way of relationship between endothelial dysfunction and pulmonary disease severity.…”
Section: Discussionsupporting
confidence: 64%
“…Indeed, adding a D-dimer cut-off beyond 500 ng/mL to female gender and absence of pneumonia at CT scan could exclude COVID-19 diagnosis with a high sensitivity and speci city (4). Moreover, we and others previously showed that D-dimer level at admission was higher in patients needing ICU referral compared to those who did not require it (5,20).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The hypothesis of microthrombi in kidneys was also suggested in COVID‐19 patients because high creatinine level was correlated with D‐dimers above 500 ng/mL 9 . Finally, endothelial dysfunction might also play a role in the incidence of severe respiratory symptoms and viral systemic dissemination 10 . Indeed, the SARS‐CoV‐2 receptor ACE2 is strongly expressed on endothelial cells 11 .…”
Section: Introductionmentioning
confidence: 97%
“…Indeed, SARS-CoV-2 can infect cells by angiotensin-converting enzyme 2 receptor, largely expressed in endothelial cells. 6,7 An endotheliitis has been hypothesized as the origin of compromised microcirculation affecting lungs and kidneys in COVID-19. 7 Endothelial cells' infection could trigger activation of coagulation and diffuse microthrombosis.…”
Section: Discussionmentioning
confidence: 99%